The Impact of Followers' Actions and Reactions on Influencer - Saebah, Nur; Suhardiman, Suhardiman; Rizki, Muhammad (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This research aims to analyze the sequential influence of stimuli in the form of product posts and beauty influencers on social media that influence various organizations, giving rise to responses in the form of intentions to follow beauty influencer accounts, imitate the beauty influencer's lifestyle, and recommend the beauty influencer. Researchers used quantitative data to collect primary data using survey methods and questionnaires filled out by respondents, distributed online using Google Forms. The research results show that brand-influencer compatibility positively influences followers' perceptions of advertising posts, followers' perceptions of influencer credibility and the influencers themselves. Perception of advertising posts also positively influences followers' perceptions of the influencer's credibility and perceptions of followers' behavior towards the influencer. Likewise, the credibility of influencers positively influences followers' behavior towards influencers and followers' intentions to continue following accounts, imitating influencers, and recommending influencers to others. Meanwhile, followers' behavior towards influencers positively affects followers' intentions to continue following accounts, imitating influencers, and recommending influencers to others.